Political relationship and narrative knowledge : a critical analysis of school authoritarianism - Armitage, Peter B., 1939- (Critical studies in education and culture series., 2000)
Annotation A model of hope for teachers struggling against inhumane and authoritarian bureaucracies, applying Habermas's critique of prevailing technocratic schooling and its danger to the public sphere of reason.